An alternative approach for nitrate and arsenic removal from wastewater via a nitrate-dependent ferrous oxidation process. (15th August 2018) - Zhang, Meilin; Li, Yingfen; Long, Xinxian; Chong, Yunxiao; Yu, Guangwei; He, Zihao
Abstract: Owing to the high efficiency of converting nitrate to nitrogen gas with ferrous iron as the electron donor, the process of nitrate-dependent ferrous oxidation (NDFeO) has been considered suitable to treat wastewater that contains nitrate but lacks organic matter. Meanwhile, arsenic immobilization often has been found during the NDFeO reaction. Thus, it was strongly expected that nitrate and arsenic could be removed simultaneously in co-contaminated wastewater through the NDFeO process. However, in the current work, arsenic was not removed during the NDFeO process when the pH was high (above 8), though the nitrate reduction rate was over 90%. Meanwhile, the biosolid particles from the NDFeO process demonstrated strong adsorption ability for arsenic when the pH was below 6. Yet, the adsorption became weak when the pH was above 7. Fourier transform infrared (FTIR) spectroscopy analysis revealed that the main activated component for arsenic adsorption was iron oxide in these particles, which was easily crippled under high pH conditions. These results implied that co-removal of nitrate and arsenic in wastewater treatment using NDFeO was difficult to carry out under high pH conditions. Thus, a two-step approach in which nitrate was removed first by NDFeO followed by arsenic adsorption with NDFeO biosolids was more feasible. Graphical abstract: Image 1 Highlights: Nitrate-dependent ferrous oxidation (NDFeO) at high pH could not effectively clear As. The co-removal of nitrate and As in wastewater treatment with NDFeO was difficult. Biosolid particles from the NDFeO process proved to be excellent As adsorbents. For removal of nitrate and As, a two-step approach based on NDFeO is presented.